The Occurrence Of Corrosion Problem In Oil Production Equipment Caused By Sulfate Reducing Bacteria And Dissolved Oxygen - Nuraini Nuraini; Febrianto Febrianto (Testing Center for Oil and Gas LEMIGAS, 2009)
One of most problems occur in oil production equipments is corrosion that is caused by some factors, such as the existence of sulfate reducing bacteria and dissolved oxygen in injection water. Based on the results of laboratory, A–GS and R–GS contain 0.90 ppm and 1.19 ppm dissolved oxygen and have potential to form corrosion problem, except D–GS with 0 ppm dissolved oxygen and no corrosion problem. After SRB tests, A–GS tube appearance colour is not black, because SRB is not found in the A–GS injection water. Whereas, R–GS and D–GS contain SRB with sulfate reducers > 100,000, therefore R–GS and D–GS tubes appearance colour are completely black